Isolation and identification of antagonistic bacteria from phylloplane of rice as biocontrol agents for sheath blight - Akter, Shamima; Kadir, Jugah; Juraimi, Abdul Shukor; Mohd Saud, Halimi; Elmahdi, Salha (Triveni Enterprises, 2014)
A total of 325 bacteria were isolated from both healthy and sheath blight infected leaf samples of rice plants, collected from different places of Malaysia, following dilution technique. Sheath blight pathogen was isolated from infected samples by tissue plating method. Out of 325, 14 isolates were found to be antagonist against the pathogen in pre evaluation test. All the 14 isolates were morphologically characterized. Antagonistic activity of these isolates was further confirmed by adopting the standard dual culture and extracellular metabolite tests. The best isolates were selected, based on the results. In dual culture test, the selected bacterial isolates KMB25, TMB33, PMB38, UMB20 and BMB42 showed 68.44%, 60.89%, 60.22%, 50.00% and 48.22% fungal growth inhibition, respectively and in extracellular metabolite test these bacterial isolates exhibited 93.33%, 84.26%, 69.82%, 67.96% and 39.26% of the same, respectively. Biochemical tests of selected isolates were performed following standard procedure. These bacterial isolates were tentatively identified as fluorescent pseudomonas by morphological and biochemical characterization. The identities were further confirmed by Biolog microstation system as P. fluorescens (UMB20), P. aeruginosa (KMB25, TMB33 and PMB38) and P. asplenii (BMB42) with similarity index ranging from 0.517 to 0.697. The effective bacterial isolates obtained from the present study can be used in the management of soil borne fungal pathogen Rhizoctonia solani, causing sheath blight of rice.